Developing Android Role Playing Game for Elementary Music Learning - Nugraha, R. Gita Ardhy; Sumaryanto, Totok; Utomo, Kamsijo Budi (Harmonia: Journal of Arts Research and Education, 2018)
Elementary students prefer to listen to modern songs from the device that they have in their daily life. In the music learning process, the student feels bored because of the monotone learning method, even though the music art learning process is an important process to promote student knowledge about IndonesiaÃ¢â‚¬â„¢s traditional songs. Innovation is needed because of this condition. This study aims to design and develop an android role-playing game (RPG) for music learning, especially IndonesiaÃ¢â‚¬â„¢s traditional songs. This study also analyses the worthiness of android RPG game based on expert judgment validationÃ¢â‚¬â„¢s score. Based on expert judgment validationÃ¢â‚¬â„¢s score, the music art learning media called Ã¢â‚¬Å“Lagu NusantaraÃ¢â‚¬Â is worthy of supporting the student to learn about the basic of music learning and IndonesiaÃ¢â‚¬â„¢s traditional songs. The average score is 3.6 for media representation, 4 for the material which presented in this game, and 3.3 for the use of language. The worthiness of this media is above 90% (precisely 90.83%). In conclusion, this RPG game can use by teachers or students to promote music art learning process, especially about IndonesiaÃ¢â‚¬â„¢s traditional songs.